THE INFLUENCE OF THE WORK ENVIRONMENT, ORGANIZATIONAL CULTURE AND ORGANIZATIONAL JUSTICE ON ORGANIZATIONAL COMMITMENT EMPLOYEES OF PT MANDIRI JOGJA INTERNASIONAL - Hidayah, Nur; Subiyanto, Didik; Purnamarini, Tri Ratna (LPPM Universitas Trunojoyo Madura, 2025)
This study examines the influence of the work environment, organizational culture, and organizational justice on organizational commitment. This study uses a quantitative method by involving all employees of PT Mandiri Jogja International, totaling 80 people, as the population and sample. The sampling technique used is saturated sampling, which is included in the category of non-probability sampling. Data collection is carried out through questionnaires, and data quality is guaranteed through validity, reliability, and classical assumption tests (including normality, multicollinearity, and heteroscedasticity). Data analysis was carried out using multiple linear regression, equipped with a T test, an F test, and a determination coefficient (R²) calculation. The results of the study show that the work environment does not have a significant positive influence on organizational commitment. In contrast, organizational culture and organizational fairness have a significant and positive influence on organizational commitment. In addition, the combined influence of the work environment, organizational culture, and organizational fairness significantly affects the organizational commitment of PT Mandiri Jogja Internasional employees.